2000
DOI: 10.1073/pnas.97.21.11638
|View full text |Cite
|
Sign up to set email alerts
|

Rice dwarf mutant d1 , which is defective in the α subunit of the heterotrimeric G protein, affects gibberellin signal transduction

Abstract: Previously, we reported that the rice dwarf mutant, d1, is defective in the ␣ subunit of the heterotrimeric G protein (G␣). In the present study, gibberellin (GA) signaling in d1 and the role of the G␣ protein in the GA-signaling pathway were investigated. Compared with the wild type, GA induction of ␣-amylase activity in aleurone cells of d1 was greatly reduced. Relative to the wild type, the GA 3-treated aleurone layer of d1 had lower expression of Ramy1A, which encodes ␣-amylase, and OsGAMYB, which encodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
290
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 351 publications
(306 citation statements)
references
References 34 publications
8
290
1
2
Order By: Relevance
“…Rice d1 mutant also has been shown to have less sensitivity to GA as it is defective in GA 3 -induced α-amylase activity in the aleurone layer [9]. Moreover, RNA blot analysis has shown three GA-inducible genes, OsMYB, Ca 2+ -ATPase and Ramy1, with a weaker response to GA in d1 mutant than in wild-type plant [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rice d1 mutant also has been shown to have less sensitivity to GA as it is defective in GA 3 -induced α-amylase activity in the aleurone layer [9]. Moreover, RNA blot analysis has shown three GA-inducible genes, OsMYB, Ca 2+ -ATPase and Ramy1, with a weaker response to GA in d1 mutant than in wild-type plant [9].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RNA blot analysis showed that GA-inducible genes, OsMYB, Ca 2+ -ATPase and Ramy1, had a weaker response to GA in the d1 mutant than that in control plants [9]. Epistatic analysis showed that slr (slender rice), caused by mutation in a crucial regulator in GA signaling, is epistatic to d1 [9]. Undoubtedly, this evidence revealed that GA signaling is affected in the d1 mutant.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The reduction in cell number in G protein mutants is compensated in many cases by cell elongation to achieve nearly normal morphology. Nonetheless, G protein mutants have altered sensitivities to several hormones (Ashikari et al, 1999;Fujisawa et al, 1999;Ueguchi-Tanaka et al, 2000;Ullah et al, 2001Ullah et al, , 2002Ullah et al, , 2003Wang et al, 2001). The reduced perception of some hormones and the complete loss in others in the G protein mutants must impact cellular responsiveness to many signals.…”
Section: Resultsmentioning
confidence: 99%
“…GAs consist of a large family of tetracyclic diterpenoids and are associated with a number of plant growth and developmental processes such as seed germination, stem elongation, flowering and fruit development (Reid 1993, Hooley 1994, Ross et al 1997. To date, we have screened and characterized several rice GArelated mutants and isolated the genes involved in GA biosynthesis and signal transduction in the rice plant (Ashikari et al 1999, Ueguchi-Tanaka et al 2000, Ikeda et al 2001, Itoh et al 2001. Through these studies, we recognized that the plant morphology of the sd1 mutants was similar to that of GA-deficient mutants with a weak phenotype.…”
Section: Physiological Characterization Of Sd1mentioning
confidence: 99%